Different activation in left dorsolateral prefrontal cortex and left orbitofrontal cortex during autobiographical memory tasks is associated with depressive disorder with different levels of resilience: a functional near-infrared spectroscopy study - Wu, Huifen; Lu, Baoquan; Xiang, Nian; Qiu, Min; Da, Hui; Xiao, Qiang; Zhang, Yan; Shi, Hui (Frontiers in Psychology, 2025)
ObjectivePrevious studies have found that resilience is a protective factor against depression, and new antidepressant methods can be developed from the perspective of resilience. However, it remains unclear how resilience protects individuals from depressive symptoms and what neural mechanisms underlie this “protective” effect.MethodsWe recruited 237 participants in our study according to the depression and anxiety clinical scale (HADS) and Connor-Davidson Resilience Scale (CD-RISC), including 100 healthy controls (HADS≤7) and 137 depressed patients (HADS≥8). All participants were evaluated using 53-channel functional near-infrared spectroscopy (fNIRS) to detect cerebral hemodynamic differences during autobiographical memory tasks.ResultsThe results showed that (1) the activation of oxy-Hb in the left dorsolateral prefrontal cortex (DLPFC) was significantly higher in the positive emotional valence condition than in the negative emotional valence condition for the groups of depression-high resilience and healthy-low resilience, while there was no significant difference between the positive and negative emotional valences observed in response to for the groups of depression-low resilience and healthy-high resilience. (2) Oxy-Hb activation under positive emotional valence was significantly higher in the group with healthy-low resilience than healthy-high resilience and depression-low resilience. (3) Under the negative emotional valence condition, resilience mediated the indirect effect of depression on oxy-Hb activation in the left orbitofrontal cortex (OFC).ConclusionfNIRS may be a useful tool for diagnosing and characterizing depression in patients with high or low resilience and improving individual resilience may be a new perspective for diagnosing and intervening in depression.